2020
DOI: 10.3390/molecules25143176
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Plasma Surface Activation of Aligned Electrospun PLGA Fiber Fleeces with Improved Adhesion and Infiltration of Amniotic Epithelial Stem Cells Maintaining their Teno-inductive Potential

Abstract: Electrospun PLGA microfibers with adequate intrinsic physical features (fiber alignment and diameter) have been shown to boost teno-differentiation and may represent a promising solution for tendon tissue engineering. However, the hydrophobic properties of PLGA may be adjusted through specific treatments to improve cell biodisponibility. In this study, electrospun PLGA with highly aligned microfibers were cold atmospheric plasma (CAP)-treated by varying the treatment exposure time (30, 60, and 90 s) and the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 129 publications
(217 reference statements)
4
38
0
Order By: Relevance
“…Cells orientation of AECs cells after 14 days of culture with CM CO and CM FZ under air and physoxia condition was assessed on the obtained 3D tendon-like structures using the Directionality Plugin of ImageJ (Sensini et al, 2018 ; El Khatib et al, 2020 ), to better determine the teno-inductive properties of CMs. Briefly, Plugin chops the IHC images with cells nuclei DAPI counterstained into square pieces and computes their Fourier power spectra allowing the generation of statistics data on the basis of the highest peak found represented by direction (the center of the Gaussian) and dispersion (the standard deviation of the Gaussian).…”
Section: Methodsmentioning
confidence: 99%
“…Cells orientation of AECs cells after 14 days of culture with CM CO and CM FZ under air and physoxia condition was assessed on the obtained 3D tendon-like structures using the Directionality Plugin of ImageJ (Sensini et al, 2018 ; El Khatib et al, 2020 ), to better determine the teno-inductive properties of CMs. Briefly, Plugin chops the IHC images with cells nuclei DAPI counterstained into square pieces and computes their Fourier power spectra allowing the generation of statistics data on the basis of the highest peak found represented by direction (the center of the Gaussian) and dispersion (the standard deviation of the Gaussian).…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, it was verified that tendon biomimetic electrospun PLGA scaffolds with highly aligned fibers and adequate fiber diameter size (ha-PLGA) possess mechanical properties that are similar to human tendons [10,13,14]. Moreover, it was demonstrated that the developed constructs are suitable for inducing the differentiation of ovine amniotic epithelial stem cells (oAECs) towards the tenogenic lineage and for boosting their immunomodulatory properties by enhancing anti-inflammatory interleukin production [10,14], crucial for tendon regeneration.…”
Section: Introductionmentioning
confidence: 94%
“…Different polymers including poly( -caprolactone) (PCL), poly(lactic acid) (PLA), and poly(lactide-co-glycolide) (PLGA) are FDA-approved polymers that have been widely applied for biomedical and in particular tendon applications [1,2,[4][5][6][7][8][9][10][11][12][13][14]. Although PLA and PCL are two biocompatible polymers, they are characterized by high hydrophobic properties that decreased cell adhesion due to the lack of cell recognition sites on their surfaces [9,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, these polymers are mostly inexpensive, can be scaled industrially, and are thermoplastic, making them moldable and allowing the development of a wide variety of different structures [317,329,330]. Synthetic materials are common in tendon tissue engineering and belong mostly to aliphatic polyesters such as polyglycolic acids (PGA), polylactic acids (PLA), and polycaprolactones (PCL), as well as their copolymers poly (lactic-co-glycolic) acids (PLGA) and poly (lactic-co-caprolactone) acids (PLCL) [329,[331][332][333][334]. Other materials are also used such as Poly (ester urethane) urea (PEUUR) [335,336], polyurethane (PU) [337], and polyethylene oxide (PEO) [338][339][340].…”
Section: (1) Natural Polymersmentioning
confidence: 99%
“…Different traditional techniques have been used to fabricate scaffolds for tendon regeneration including sponges [341][342][343], freeze-drying [323,324,344,345], supercritical fluid processing [346,347], extruding [348], electrochemically aligned collagen [319,349,350], and electrospinning [322,325,332,333,351,352]. Recently, 3D bioprinting has emerged as an novel technique in the field of tissue engineering aiming at fabricating organized scaffolds with complex shapes [352][353][354][355][356].…”
Section: Scaffold Fabricationmentioning
confidence: 99%